The development of inquiry-based mathematics teaching materials for space figures for elementary schools - Evi Apriani; Agus Susanta; Irwan Koto (International Journal of Trends in Mathematics Education Research, 2022)
This study aims to develop inquiry-based worksheets on the material area and volume of cylinder shapes that are valid, feasible, effective, and improve learning outcomes. This research is a research and development (RD) using the ADDIE model, which consists of 5 stages: the Analysis, Design, Develop, Implement, and Evaluate stages. Subjects in the study were grade VI students of SD Negeri 2 Bengkulu City. The research instrument used a validation sheet, a teacher and student response questionnaire, and a question test sheet. The research data were then analyzed using descriptive analysis. The results showed that the inquiry-based LKPD products that had been developed and assessed by expert validators were in the very valid category with an average percentage of 94.79%; the teacher's response to the guided inquiry-based LKPD obtained a percentage of 80.0% with appropriate categories or criteria, and student responses to guided inquiry-based LKPD received a percentage of 74.62% in the appropriate category and an effective level of 80.95% in the effective category. Thus, it can be concluded that the inquiry-based students' worksheets on the cylinder shapes developed are very valid, feasible, effective, and can improve student learning outcomes to be used as supporting teaching materials in the learning process. Finally, these inquiry-based student worksheets are expected to be used as a basic framework for developing students' worksheets for other materials.